Analisis Penentuan Perbandingan Kepuasan Pelanggan Pada Toko Budiman, Nella Mart, Dan Raja Mart Di Kota Payakumbuh Dengan Metode Analisis Korespondensi - Widia Khairani; Muhammad Alung; Syuryatman Desri (Journal of Management and Creative Business, 2023)
This study aims to see a comparison of customer satisfaction for retail stores such as Toko Budiman, Nella Mart, and Raja Mart. The data used is primary data by distributing questionnaires to respondents who have done shopping activities in each of these retail stores. There are ten attributes/variables used in determining customer satisfaction, namely, satisfaction with product variety, service, catalog, strategic location, cleanliness, store space, price, discount, parking, and light. In this study, the correspondence analysis method was used to find and display relationships between categories or variables, which were processed using the SPSS 26.0 application.